2021
DOI: 10.1371/journal.pntd.0009329
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening individual and family resilience against leprosy-related discrimination: A pilot intervention study

Abstract: Background Leprosy and leprosy-related stigma can have a major impact on psychosocial wellbeing of persons affected and their family members. Resilience is a process that incorporates many of the core skills and abilities which may enable people to address stigma and discrimination. The current study aimed to develop and pilot an intervention to strengthen individual and family resilience against leprosy-related discrimination. Methodology We used a quasi-experimental, before-after study design with a mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…All the studies used a qualitative approach or had a clearly reported qualitative component. There were nine studies based on the phenomenological approach [12,19,43,49,56,58,62,80,87], two were ethnographic studies [63,68], two used the grounded theory approach [55,78], and six were mixed methods [14,34,51,53,57,79], but only the India and Indonesia 1 [79] https://doi.org/10.1371/journal.pntd.0010761.t002…”
Section: Study Inclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…All the studies used a qualitative approach or had a clearly reported qualitative component. There were nine studies based on the phenomenological approach [12,19,43,49,56,58,62,80,87], two were ethnographic studies [63,68], two used the grounded theory approach [55,78], and six were mixed methods [14,34,51,53,57,79], but only the India and Indonesia 1 [79] https://doi.org/10.1371/journal.pntd.0010761.t002…”
Section: Study Inclusionmentioning
confidence: 99%
“…The most frequently absent detail in the included studies was the information on the influence of the researcher on the research (question 7, S5 Appendix); only five studies reported this item. [34,45,58,62,73] Seventeen studies [12,19,43,44,47,59,63,65,[69][70][71][75][76][77]79,80,83] had no obvious statement locating the researcher culturally or theoretically.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…9 These effects manifest at the individual, family, and community levels. 11,12 At the individual level, persons affected may experience emotional stress and anxiety, which may lead to psychological and psychiatric morbidity. 13,14 At the community level, social participation can be restricted with difficulties related to community interaction, social relationships such as friendship and marriage (prospects), and employment.…”
Section: Introductionmentioning
confidence: 99%